Lithuanian Speech Synthesis by Computer using Additive Synthesis - Pyz, G.; Simonyte, V.; Slivinskas, V. (Elektronika ir Elektrotechnika, 2012)
We present a new Lithuanian speech phoneme synthesis method based on the principle of additive synthesis in this paper. An assumption is made that phoneme models consist of the sum of harmonics which could be generated by properly chosen formant synthesizer parameters. In order to estimate the synthesizer parameters, we use the real sound signals that are expanded into harmonics by the inverse fast Fourier transform method. The harmonic synthesizer parameters (amplitudes, damping factor, and phases) are estimated by Levenberg-Marquardt method. We present an example of the synthesized female vowel /a/ and compare it with the true sound signal. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2631